2015
DOI: 10.1080/13571516.2014.982901
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Financial Crisis on Banking Acquisitions: A Look at Shareholder Wealth

Abstract: This paper examines the influence of the 2007-08 financial crisis on value creation for acquirer's shareholders in the banking industry using a sample of 883 deals over 2004-12. Applying an exploratory and top-down approach, banking acquisitions are considered at the global level, narrowing the analysis step by step to consider domestic versus cross-border acquisitions. Then cross-border deals are split based on the economic development of the acquirer and target countries. It is observed that only acquisition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 99 publications
1
9
0
Order By: Relevance
“…Also, recent studies have shown that the turbulences in the business environment can have a significant impact on bidder's returns (Beltratti & Paladino, 2013;Rao-Nicholson & Salaber, 2014a, 2014b, 2015Wan & Yiu, 2009). Thus, it is interesting to look at the impact of the 2007-2008 financial crisis on the OP of M&As in ASEAN.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Also, recent studies have shown that the turbulences in the business environment can have a significant impact on bidder's returns (Beltratti & Paladino, 2013;Rao-Nicholson & Salaber, 2014a, 2014b, 2015Wan & Yiu, 2009). Thus, it is interesting to look at the impact of the 2007-2008 financial crisis on the OP of M&As in ASEAN.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…[2] suggests that M&A activities are not closely related to the business cycle but the state of the economy. In other words, if economy is in a good condition, stock markets have desired conditions for the firms to raise capital and grow their profitability [3]. On the other hand, in the opposite situation, that is, if economy is in a narrow condition, firms tend to be more conservative about M&A.…”
Section: Mergers and Acquisitions During Financial Crisismentioning
confidence: 96%
“…Abnormal returns precrisis and postcrisis period was not significantly different from zero. In another research, [3] examined 883 cross-border M&A deals in banking sector between 2004 and 2012. They concluded that only in M&As from emerging countries targeting developed countries, returns of the shareholders were significantly positive after the crisis.…”
Section: Abnormal Returns Of Cross-border Mandas During Financial Crisismentioning
confidence: 99%
See 2 more Smart Citations